Customer relationship management (CRM) and passenger loyalty in delivering high quality service at Air Namibia: A structural equations approach - Isaacs, Albert J; Lwendo, S B; Kazembe, Lawrence (Namibian Journal for Research, Science and Technology, 2022)
Air Namibia, like any other airline, faces challenges as it operates in the global economy. Extreme scrutiny and debate about Air Namibia’s viability has highlighted some of the airline’s major issues of strategic, operational inefficiency and inability to create customer value. The study’s aim was to establish the impact of passenger loyalty on customer relationship management (CRM) in delivering high quality service to passengers and value creation. Structural equation modelling (SEM) was used to analyze survey data collected from 181 international, regional and domestic passengers using Air Namibia for passengers travelling through the Hosea Kutako International and Eros Airports. The study further identified the primary factors affecting passenger satisfaction with Air Namibia’s value chain activities, these factors included: customer orientation, operational specialties, domain expertise, and service recovery and information technology. While factors contributing to passenger retention and loyalty towards Air Namibia’s products and services included Marketing and Promotional Activities, Loyalty aspects, Value for Money and Comfort Issues. In exploring the relationship between customer relationship management (CRM) and passenger loyalty, the study found that interpersonal relationships between staff and the customers are crucial to CRM initiatives as they result in a better understanding of customer needs, which in turn leads to passenger loyalty.